The effectiveness of the Pilates method in pregnant women (Research, Society and Development, 2025)
Introduction: The practice of physical exercise during pregnancy is recommended by health organizations such as the WHO, with Pilates gaining increasing prominence. Objective: This article reviews the literature on the effectiveness of the Pilates method in pregnant women, focusing on its musculoskeletal benefits, respiratory control, and emotional aspects. Materials and Methods: The methodology consisted of a non-systematic review of articles published between 2010 and 2021, selected from databases such as Google Scholar and SciELO, using descriptors related to physiotherapy, Pilates, and pregnancy. Results: The results indicate that Pilates contributes to core muscle strengthening, relieving lower back pain and improving flexibility and balance. Additionally, respiratory control during exercises helps with relaxation and preparation for childbirth, while psychological benefits include reduced anxiety and stress. The practice also enhances sleep quality, which is essential for the overall well-being of pregnant women. Conclusion: It is concluded that Pilates, when performed under professional supervision, is a safe and effective tool for promoting a healthier and more comfortable pregnancy. Its positive effects on musculature, pain management, and mental health make it a recommended practice during prenatal care, with benefits extending into the postpartum period. Further studies are suggested to consolidate the existing evidence and explore long-term effects.